Recognition of non-formal and informal learning in Europe - criteria-based comparison of selected approaches - Annen, Silvia [Verfasser] (My University, 2010)
"In this paper selected approaches for the recognition of non-formal and informal learning are analysed and compared with regard to theoretically well-founded criteria. Thereby the focus lies on approaches which are not anchored within the formal educational system, but which provide a certification of learning outcomes. Therefore, three approaches were selected: the European Computer Driving Licence (ECDL), the European Business Competence Licence (EBC*L) and the personnel certification within the Advanced IT Training System (AITTS). The first two approaches were developed on a European level while the AITTS is a German approach. Within the analysis the following criteria are included: context of the development, objectives, understanding of competence, methods, stakeholders, rights of disposal, coordination, norms and standards. After a brief description of the selected approaches they are compared with the help of these criteria. The results of the comparison are used to think about the future development of approaches like the analysed ones and give recommendations for a better integration in the formal educational system." (Autorenreferat, BIBB-Doku)
Keywords: S 2.2.4.4 Anerkennung non-formaler Qualifikationen; L 2.1.1 Informelles Lernen; I 2.2 Europa; Informelles Lernen; Anerkennung; Lernergebnisorientierung; Informationstechnische Bildung; Ökonomische Bildung; IT-Weiterbildung; Europa